INNOVATION IN FERMENTED FUNCTIONAL BEVERAGES BASED ON NUTMEG SEEDS (Myristica Fragrans Houtt.) AND ACACIA HONEY AS A SOURCE OF NATURAL ANTIOXIDANTS: INOVASI DALAM MINUMAN FUNGSIONAL FERMENTASI BERBASIS BIJI PALA (Myristica Fragrans Houtt.) DAN MADU AKASIA SEBAGAI SUMBER ANTIOKSIDAN ALAMI - Dodi Iskandar (ROCE : Jurnal Pertanian Terapan, 2026)
Nutmeg seeds (Myristica fragrans Houtt.) are rich in bioactive compounds and have strong potential for development as functional beverages. This study evaluated the effects of formulation ratio and fermentation duration on the physicochemical characteristics and antioxidant activity of a fermented nutmeg seed beverage supplemented with acacia honey. Three formulations with different nutmeg seed–acacia honey ratios were subjected to anaerobic fermentation for 15 and 30 days, followed by analysis of moisture content, sugar content, total acidity, insoluble solids, ash content, and antioxidant activity using the DPPH method (IC₅₀), with data evaluated by analysis of variance (ANOVA). The results showed that fermentation duration significantly affected moisture content, total acidity, ash content, and antioxidant activity (p < 0.05), while formulation ratio significantly influenced insoluble solid content and antioxidant performance. Moisture content ranged from 0.27% to 0.91%, sugar content from 0.64% to 0.75%, total acidity from 165.26 to 179.21, insoluble solids from 1.46% to 5.63%, and ash content from 0.17% to 0.93%. Antioxidant activity showed IC₅₀ values ranging from 56.85 to 148.59 μg/mL, with the highest activity observed in the formulation containing equal proportions of nutmeg seeds and acacia honey fermented for 30 days. These findings indicate that fermented nutmeg–acacia honey beverages possess promising functional properties, with formulation composition and fermentation time playing critical roles in optimizing antioxidant activity